The Economic Consequences of Determining the Scope of Copyright Protection on the Background of selected Judicial Decisions - Nowak-Gruca , Aleksandra (Studia Oeconomica Posnaniensia, 2015)
Copyright today is facing an unsolved problem; the need to provide incentives for creative activities at the lowest cost to society associated with the legal protection of copyright holders to prevent others from freely using protected works; including concerns stemming from the existence of monopolies. The central issue presented in this paper is what economic analysis has to offer the field of copyright protection regarding intellectual works with levels of creativity and originality that are negligible.